PENGARUH SEKTOR PARIWISATA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN LOMBOK TENGAH DAN KABUPATEN MALANG - Kurnia Putri Faranita Sari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Tourism is one of the strategic sectors that can develop the regional economy in accordance with the potential of the area, as well as in Central Lombok Regency and Malang Regency. This study aims to determine the difference between the tourism sector and economic growth in Central Lombok Regency and Malang Regency. This study uses data on the number of tourists, the number of hotels, and road infrastructure to describe the tourism sector. While THE GRDP is used as a bound variable. The method used is multiple linear regression analysis with time series data from 2011-2020. This research shows that the number of tourists has no effect on GRDP in Central Lombok Regency and Malang Regency. The number of hotels has a positive and significant effect on GRDP in Central Lombok Regency and Malang Regency. Meanwhile, road infrastructure has a positive and significant effect on GRDP in Central Lombok Regency, but in Malang Regency, road infrastructure does not affect GRDP.